Rapidity Correlation of K/π to ϕ in γSCSM and Pythia - Doroci,Leutrim (2025)
Pythia with Rope Hadronization, and the Canonical-Statistical Model with strangeness undersaturation (γSCSM), have shown remarkably similar results when simulating strange hadrons yields relative to pion yields as a function of event-multiplicity. As the underlying assumptions in these models are very different, a novel observable is warranted. The aim of this thesis is to show that K0S/(π+ + π−) in ϕ-triggered events is an observable which distinguishes between Pythia and γSCSM. For this purpose K0S/(π+ + π−) in three rapidity windows w.r.t ϕ was studied in proton-proton collisions, namely, |∆y| < 0.1, |∆y| < 0.5 and |∆y| < 1 as a function of event multiplicity. With these considerations, stark differences were observed between the two models. The Lund String Model implemented with Pythia conserves strangeness on the level of string breaks, which results in larger K0S yields relative to π+ + π− in regions closer to ϕ. Contrary to this, the statistical nature of γSCSM does not predict any increase of K0/π in ϕ-triggered events when compared to non-triggered events. Moreover, Pythia events were generated for multiple values of the vector-meson mixing angle (θV ). This allowed for a study of ϕ/π based on the probability of ss¯, uu¯ or d¯d projecting onto ϕ, and how that affects K0S/(π+ +π−) in the different rapidity windows. Here it was observed that larger deviations from ideal-mixing(θV = 35.3◦) resulted in larger ϕ/π, whilst only minimal decreases in K0S/(π+ + π−) were noticed.